Rangka tindakan ekonomi digital membina kekayaaan dala era e-niaga - Tapscott, Don; Lowy, Alex; Ticoll, David
"Following Tapscott's introduction, each chapter of Blueprint is authored by a member of the Alliance, all senior strategists and CEOs from today's most influential businesses--companies such as General Motors, Hewlett-Packard, IBM, MCI, and Nortel. Each covers a core area of the digital revolution, such as the transformation of financial services or the use of networks to improve organizational agility